Defining the purpose of a speech and choosing a topic in sports journalism - Abdurahimova Nozimakhon Bahadirovna; Fayziev Davron Ahmedjanovich (Genius Journals, 2022)
At present, Uzbek sports journalism does not have manuals and books on the purpose of speech, and the purpose of this article is to find clarity in this area and to expand it. There is research and guidance in both national and foreign languages on the purpose of the speech and the choice of topic in other areas of journalism. They can see the strengths and weaknesses of their chosen path and correct them, but sports journalism is unforgivable. This is because the topics in sports journalism are always exciting, hot and emotional. When the purpose of the speech is not clear, the power to deliver sporting events to the listener is ineffective
Keywords: Uzbek sport journalism; Uzbek Sport; Sport Journalism; Speech in sport journalism